Prevalence and correlates of current suicide risk in an international sample of OCD adults: A report from the International College of Obsessive-Compulsive Spectrum Disorders (ICOCS) network and Obsessive Compulsive and Related Disorders Network (OCRN) of the European College of Neuropsychopharmacology. (August 2021) - Benatti, Beatrice; Dell'Osso, Bernardo; Shen, Hanyang; Filippou-Frye, Maria; Varias, Andrea; Sanchez, Catherine; Jo, Booil; Hollander, Eric; Fineberg, Naomi A.; Stein, Dan J.; Nicolini, Humberto; Lanzagorta, Nuria; et al.
Abstract: Introduction: Obsessive-compulsive disorder (OCD), characterized by repetitive anxiety-inducing intrusive thoughts and compulsive behaviors, is associated with higher suicide ideation and suicide attempts than the general population. This study investigates the prevalence and the correlates of current suicide risk in adult outpatients in an international multisite cross-sectional sample of OCD outpatients. Methods: Data were derived from the International College of Obsessive-Compulsive Spectrum Disorders (ICOCS) network's cross-sectional data set (N = 409). Current suicide risk (assessed by Item C of the MINI) and diagnoses of psychiatric disorders were based on DSM-IV. Chi-squared test for categorical variables and t -test for continuous variables were used to make statistical inferences about main features associated with current suicide risk. P < .05 was considered as statistically significant. Results: The prevalence of current suicidal risk was 15.9%, with equal likelihood in sociodemographic variables, including age and gender. Increased rates of major depression and generalized anxiety disorder were associated to higher current suicide risk. Current suicide risk was also associated with higher severity of OCD, depressive comorbidity, and higher levels of disability. There were no significant differences in treatment correlates—including type of treatment and psychiatric hospitalizations—between the groups of individuals with and without current suicide risk. Conclusion: Our findings suggest that current suicide risk is common in patients with OCD and associated with various forms of pathology. Our work also provides further empirical data to support what is already known clinically: a worse clinical picture characterized by a high severity of OCD, high distress related to obsessions and compulsions, and the presence of comorbidities such as major depression and generalized anxiety disorder should be considered as relevant risk factors for suicide risk.